PENGARUH WHISTLEBLOWING SYSTEM, KEMAMPUAN AUDITOR, SKEPTISME AUDITOR, DAN INDEPENDENSI TERHADAP PENDETEKSIAN KECURANGAN - Nur Muchlisiah Utami Magister Akuntansi Pascasarjana, U (Bongaya Journal for Research in Accounting (BJRA), 2019)
This research was conducted by aiming to determine the effect ofwhistleblowing systems, auditor capabilities, auditor professional skepticism andindependence of fraud detection. This study uses primary data using a questionnaire of33 auditors as a sample of all auditor numbers as many as 48 auditors working at theInspectorate Office of South Sulawesi Province. Data analysis using multiple regressionwith the help of SPSS software. The results of this study indicate that: (1) Whistleblowingsystems have a positive and significant effect on fraud detection: (2) The auditor's abilityhas a positive and significant effect on fraud detection: (3) The auditor's professionalskepticism has a positive and significant effect on fraud detection: (4) Independencepositive and significant effect on fraud detection.